Antimicrobial treatment improves tryptophan metabolism and mood of patients with small intestinal bacterial overgrowth - Chojnacki, Cezary; Popławski, Tomasz; Konrad, Paulina; Fila, Michał; Błasiak, Janusz; Chojnacki, Jan (Nutrition & metabolism, 2022)
Background Optimal composition of intestinal bacteria is an essential condition for good health. Excessive growth of these bacteria can cause various ailments. The aim of this study was to assess the mental state and gastrointestinal complaints of patients with small intestinal bacterial overgrowth (SIBO) in relation to tryptophan metabolism and rifaximin treatment. Methods 120 subjects, aged 23–61 years, were enrolled in the study, and divided into 3 groups, 40 individuals each: healthy subjects (Controls), patients with SIBO and chronic diarrhea (SIBO-D), and with chronic constipation (SIBO-C). The lactulose hydrogen breath test (LHBT) was performed to diagnose SIBO. The mental state of patients was assessed using the Hamilton Anxiety Rating Scale (HAM-A), and the Hamilton Depression Rating Scale (HAM-D). L-tryptophan (TRP) and its metabolites: 5-hydroxyindoleacetic acid (5-HIAA), kynurenine (KYN), xanthurenic acid (XA) and quinolinic acid (QA) were measured in urine by liquid-chromatography-tandem mass spectrometry and related to creatinine level. Patients with SIBO were recommended to take rifaximin for 10 days at daily dose 1200 mg, and this cycle was repeated in subsequent two months. Results Mild and moderate anxiety, as well as mild depression were diagnosed in all SIBO patients. Changes in TRP metabolism were also observed in these patients. Specifically, an increase in the activity of the serotonin pathway of TRP metabolism in the group SIBO-D was observed. The SIBO-C patients showed an increase in the concentration of KYN, XA and QA. 5-HIAA/TRP and KYN/TRP ratios significantly decreased in group SIBO-D, and KYN and QA levels decreased in group SIBO-C after treatment with rifaximin. The levels of anxiety and depression decreased in both groups. Conclusion Rifaximin treatment of SIBO patients ameliorated their mood disorders and gastrointestinal aliments underlined by changes in tryptophan metabolism. Trial registration Retrospectively registered (if applicable).